Alternatives to restrictive feeding practices to promote self‐regulation in childhood: a developmental perspective. Issue 5 (25th September 2015) - Rollins, B. Y.; Savage, J. S.; Fisher, J. O.; Birch, L. L.
Abstract: Intake of energy‐dense snack foods is high among US children. Although the use of restrictive feeding practices has been shown to be counterproductive, there is very limited evidence for effective alternatives to restriction that help children moderate their intake of these foods and that facilitate the development of self‐regulation in childhood. The developmental literature on parenting and child outcomes may provide insights into alternatives to restrictive feeding practices. This review paper uses a model of parental control from the child development and parenting literatures to (i) operationally define restrictive feeding practices; (ii) summarize current evidence for antecedents and effects of parental restriction use on children's eating behaviours and weight status, and (iii) highlight alternative feeding practices that may facilitate the development of children's self‐regulation and moderate children's intake of palatable snack foods. We also discuss recent empirical evidence highlighting the role of child temperament and food motivation related behaviours as factors that prompt parents to use restrictive feeding practices and, yet, may increase children's dysregulated intake of forbidden foods.